Composition of Mobile Phosphate Fractions in Soils of the Pre-Carpathians Influenced by Drainage, lime and Phosphate Fertilizer//Springer Nature // Soil Science Working for a Living - Tsvyk, Tatiana (Springer Nature, 2017)
Specific factors and conditions of soil formation in the Pre-Carpathians have caused the prevalence of iron and aluminum phosphate fractions and a low incidence of calcium phosphate. Given that present soil phosphate status is not satisfactory for agriculture, optimization can be achieved only through fundamental change of regime and various soil properties. Changes in the space-profile of phosphate fractions in Brown podzolic gleys (Albeluvisols) are examined under different drainage conditions and after application of lime and phosphate. It is confirmed that tile drainage not only improves soil aeration but, also, significantly influences the fractional composition of phosphates.
Keywords: soil phosphate fractions, Albeluvisols, drainage, lime, ground rock phosphate